Implementing a Collaborative Learning Management Model to Increase Student Engagement in the Classroom - Aji Busono, Multazem; Muhyidin, Muhyidin; Azizi, Faiz (Universitas Nurul Jadid, 2023)
This study focuses on the application of the collaborative learning model, with the aim of analyzing how teacher dominance, limited facilities, and low student motivation affect the effectiveness of collaborative learning. A qualitative research approach with a case study method is used to explore the internal dynamics that occur in the madrasah environment. Data were collected through in-depth interviews, participatory observations, and document analysis, which were then analyzed using thematic analysis techniques to identify key emerging patterns. The results show that the dominance of teachers in student grouping inhibits the diversity of interactions required for effective collaborative learning. In addition, the limitations of facilities such as cramped classrooms and lack of technological aids exacerbate the situation, while low student motivation, influenced by external factors such as family support, poses an additional challenge in the implementation of this model. The implications of this study underscore the importance of improving teacher training, improving educational facilities, and a more holistic approach that involves families and communities in supporting collaborative learning. This research makes an important contribution to the development of more effective strategies in the implementation of collaborative learning in madrassas and similar schools in Indonesia.